Ratio of martality related to disorders hypertensive agentes, with emphasis on pre-eclampsia: a literature review (Research, Society and Development, 2022)
Objective: to verify the factors that lead to maternal mortality from direct obstetric causes, with emphasis on arterial hypertension and pre-eclampsia, and to address the possible means to improve this scenario. Methodology: this is an integrative literature review study, through searches in virtual health databases, specifically in: Scielo; PubMed, Science Direct, Lilacs. 82 articles were selected for the construction of this literature review, 75 articles were excluded considering the exclusion criteria and 7 were considered for the study. Results: regarding the analysis of the selected articles, it was possible to verify that pre-eclampsia promotes alterations in the arterial wall and generates a greater cardiovascular risk. Still, it was verified the importance of carrying out prenatal care so that early diagnosis and treatment have a positive impact on the prognosis of pregnant women and also the need for qualified professionals to provide quality care. Conclusion: it was possible to conclude that arterial hypertension, especially when associated with pre-eclampsia, is a factor that contributes considerably to the increase in maternal mortality.